The Implementation of Land Rights Grant to Adopted Children by Their Adopting Parents - Ahmad, Fadly Kaizar (Jurnal Konstatering, 2022)
The purpose of this research for: 1. To find out the implementation of land rights grants to adopted children in terms of customary law, Islamic law, civil law. 2. To find out the legitimacy of grants of land rights given to adopted children by adoptive parents. 3. To find out the legal implications of grants to adopted children regarding land rights that will be withdrawn by their adoptive parents. Research methods it usesThe approach in this study uses an empirical juridical approach. Empirical juridical research is a problem approach regarding matters that are juridical in nature and the existing facts regarding matters that are juridical in nature. Empirical legal research or sociological research is legal research that uses primary data. The research results determine that: 1) Implementation of land rights grants to adopted children in terms of customary law, Islamic law, and civil law: a. The implementation of grants according to customary law is carried out according to what is customary or customary in each region in Indonesia. b. Implementation of grants according to Islamic law. Based on the Compilation of Islamic Law Article 210 Compilation of Islamic Law grants made must comply with the provisions of that article. c. Implementation of Grants According to Civil Law. Implementation of grants according to civil law is carried out according to Article 1666 of the Civil Code. 2) Legitimacy of Adoptive Children Against Grants of Land Rights Granted by Adoptive Parents. Adoption of a child also has an impact on inheritance, changing the status of a child who is adopted to become a child of adoptive parents brings juridical consequences to inheritance. This means that the adoption of a child results in a mutual inheritance relationship between the adopted child and his adoptive parents and vice versa. In line with what has been described above, adopted children have legal force and are entitled to grants given or inheritance given by their adoptive parents if the adoption is carried out according to statutory procedures. 3) Legal implications of grants to adopted children against land rights which will be withdrawn by their adoptive parents. Basically the Civil Code does not prohibit a person from giving his inheritance to his adopted child according to the provisions of the Civil Code. Whereas in Islamic law.Keywords: Adopted; Children; Grants; Parents.